Study on the fermentation effect of Rhodotorula glutinis utilizing tofu whey wastewater and the influence of Rhodotorula glutinis on laying hens - Xu, Xifei; Liu, Wenjian; Niu, Honghong; Hua, Mei; Su, Ying; Miao, Xinyu; Chi, Yanping; Xu, Hongyan; Wang, Jinghui; Sun, Mubai; Li, Da (Frontiers in Nutrition, 2023)
Tofu whey wastewater (TWW) is the wastewater of tofu processing, which is rich in a variety of nutrients. Rhodotorula glutinis can make full use of TWW to ferment and reproduce yeast cells, produce carotenoids and other nutrients, improve the utilization value of TWW, and reduce environmental pollution and resource waste. In this study, the nutrient composition changes of TWW treated by Rhodotorula glutinis were analyzed to reformulate TWW medium, and the optimal composition and proportion of TWW medium that can improve the biomass and carotenoid production of Rhodotorula glutinis were explored. Meanwhile, the Rhodotorula glutinis liquid obtained under these conditions was used to prepare biological feed for laying hens, and the effect of Rhodotorula glutinis growing on TWW as substrate on laying performance and egg quality of laying hens were verified. The results showed that the zinc content of TWW after Rhodotorula glutinis fermentation increased by 62.30%, the phosphorus content decreased by 42.31%, and the contents of vitamin B1, B2 and B6 increased to varying degrees. The optimal fermentation conditions of Rhodotorula glutinis in the TWW medium were as follow: the initial pH was 6.40, the amount of soybean oil, glucose and zinc ions was 0.80 mL/L, 16.32 g/L and 20.52 mg/L, respectively. Under this condition, the biomass of Rhodotorula glutinis reached 2.23 g/L, the carotenoid production was 832.86 μg/g, and the number of effective viable yeast count was 7.08×107 cfu/mL. In addition, the laying performance and egg quality of laying hens fed Rhodotorula glutinis biological feed were improved. In this study, we analyzed the composition changes of TWW, optimized the fermentation conditions of Rhodotorula glutinis in TWW medium, explored the influence of Rhodotorula glutinis completely utilizing TWW on laying layers, and provided a new idea for the efficient utilization of TWW.